Clinical outcomes of extended endovascular recanalization of 16 consecutive Buerger's disease patients. (June 2019) - Kacmaz, Fehmi; Kaya, Adnan; Keskin, Muhammed; Keceoglu, Serdar; Algin, Ibrahim Halil; Yilmazkaya, Bayram; Ilkay, Erdogan
Objective: Buerger's disease is one of the worst diseases causing peripheral artery occlusions (especially lower extremity) with increased morbidity and mortality. Endovascular treatment of the diseased arteries gains preference over bypass surgery nowadays. Here, we aimed to present the clinical outcomes of 16 consecutive Buerger's disease patients underwent extended endovascular recanalization which is a new technique to restore direct blood flow to at least one foot artery, with the performance of angioplasty for each tibial and foot artery obstructions. Methods: A total of 16 consecutive patients with confirmed diagnosis of Buerger's disease that percutaneously treated in our center between February 2014 and March 2018 were included in the study. The mean age of the patients was 44.25 ± 4.28 ranging from 36 to 50 years. After physical examination and complementary diagnostic tests, performance of extended angioplasty for occluded arteries was intended to restore direct blood flow to at least one of the blow-the-knee arteries. Results: A successful extended endovascular treatment was performed in 20 of 22 limbs, achieving a technical success of 91%. All patients were successfully discharged without any complication. Mean follow-up duration was 21.43 ± 7.08 months. Reintervention was performed in one patient and minor amputation was needed in one of the failed limbs. Limb salvage rate was 100%. A significant difference was observed based on Rutherford classification, ankle brachial index, direct blood flow to foot, presence of ulcer and rest pain when compared before and after the intervention. Conclusion: We showed successful extended endovascular recanalization of Buerger's disease patients with a high technical success rate and sustained clinical improvement. Extended endovascular recanalization could be a therapeutic option in Buerger's disease patients, since they are not good candidates for surgery.